1986
DOI: 10.1002/j.1460-2075.1986.tb04226.x
|View full text |Cite
|
Sign up to set email alerts
|

Location of ‘continuous’ antigenic determinants in the protruding regions of proteins.

Abstract: A simple method is described to locate 'antigenic' peptides from the a-carbon co-ordinates of a protein, based on protrusion from the protein's globular surface. A good correlation is found between those parts of a protein which protrude and the experimentally determined antigenic peptides in myoglobin, lysozyme and myohemerythrin. A comparison is made between the use of protrusion index, mobility, solvent accessibility and hydrophilicity for predicting the most likely antigenic peptides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
148
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(154 citation statements)
references
References 21 publications
6
148
0
Order By: Relevance
“…For example, Novotny et al (1986) demonstrated that the correlation between accessible surface area (ASA) and antigenicity is superior to the correlation between backbone flexibility and antigenicity. Thornton et al (1986) showed that antigenic sites protrude considerably from the protein surface and concluded that this property is a strong characteristic of antigenicity. Laver et al (1990) reported that epitope areas span a narrow range of 650-900Å 2 , encompassing 15-22 amino acids.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Novotny et al (1986) demonstrated that the correlation between accessible surface area (ASA) and antigenicity is superior to the correlation between backbone flexibility and antigenicity. Thornton et al (1986) showed that antigenic sites protrude considerably from the protein surface and concluded that this property is a strong characteristic of antigenicity. Laver et al (1990) reported that epitope areas span a narrow range of 650-900Å 2 , encompassing 15-22 amino acids.…”
Section: Introductionmentioning
confidence: 99%
“…By varying the angle, and consequently increasing the areas of the protein that are possible, the correlation does improve. When analysed critically, the correlation simply implies that all areas of globular proteins are possible Tcell epitopes, with the exception ofloops and turns -the prominent sites for B-cell recognition [13,34,35].…”
Section: Results Analyses and Discussionmentioning
confidence: 99%
“…The protrusion indices were calculated as described by Thornton et al [13]. Sequence alignments and generation of templates were carried out by methods created by Thornton and Taylor [14].…”
Section: B Methodsmentioning
confidence: 99%
“…The amino acid sequence of the measles virus F (Richardson et al, 1986) was analysed for potential B cell epitopes using algorithms to identify regions of hydrophilicity (Kyte & Doolittle, 1982), protrusion (Thornton et aL, 1986), mobility (Karplus & Schultz, 1985) and secondary structure (Wilmot & Thornton, 1988), and the following regions were identified : residues 43 to 55, 240 to 258,358 to 373,404 to 414 and 433 to 443. Of these regions, F1:404414 was chosen as the most appropriate for consideration as a potential B cell epitope because it had the properties of high hydrophilicity, high protrusion index, high mobility and the presence of a Z-turn.…”
Section: Methodsmentioning
confidence: 99%